2012
DOI: 10.7237/sjarm/192
|View full text |Cite
|
Sign up to set email alerts
|

Ict for Agriculture Knowledge Management in Nigeria: Lessons and Strategies for Improvement

Abstract: In this century alone our world is faced with an increasingly complex challenge of feeding its growing population, while assuring an equitable and sustainable development. Scientific and technological progress is generating the knowledge and tools to make this possible. The more recent scientific revolution that is taking place at the turn of the century, based on the emergence of the new areas of science, namely in molecular biology (Biotechnology), in agroecology and sustainable agricultural production, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…The conclusion is that there is a positive relationship between mobile phone and economic development in developing countries; therefore, an increase in the number of mobile phone users leads to an increase in real GDP per capita. Nnadi et al (2012) observed that ICT is a medium that has radically improved interaction around the globe, implying the need to create a strong link characterised by the impeccable flow of information; this is because ICT improves the quality and timing of information between extension agents and farmers, rather than passing information through a long bureaucratic chain. Employing data, collected through focus group discussions and interviews with fishermen and farmers across five states in India, Mittal, Gandhi and Tripathi (2010) remarked that mobile phones enabled the respondents to receive timely information, assisting them to increase their yields.…”
Section: Literature Review: Mobile Phone Technology (Information and Communication) And Agricultural Developmentmentioning
confidence: 99%
“…The conclusion is that there is a positive relationship between mobile phone and economic development in developing countries; therefore, an increase in the number of mobile phone users leads to an increase in real GDP per capita. Nnadi et al (2012) observed that ICT is a medium that has radically improved interaction around the globe, implying the need to create a strong link characterised by the impeccable flow of information; this is because ICT improves the quality and timing of information between extension agents and farmers, rather than passing information through a long bureaucratic chain. Employing data, collected through focus group discussions and interviews with fishermen and farmers across five states in India, Mittal, Gandhi and Tripathi (2010) remarked that mobile phones enabled the respondents to receive timely information, assisting them to increase their yields.…”
Section: Literature Review: Mobile Phone Technology (Information and Communication) And Agricultural Developmentmentioning
confidence: 99%
“…To the extent that about 70 per cent of the population in Sub-Saharan Africa live in rural areas and depend on agriculture for their livelihoods (Nnadi et al, 2012), improving smallholder farmers' access to markets both locally and internationally could be one of the strategies to achieving the eight millennium development goals. Kenya in particular has 90 per cent of smallholder farmers in all but the arid regions engaging in the production of horticultural products (Mutuku et al, 2004).…”
Section: Introductionmentioning
confidence: 99%